Providing Additional Food of Dragon Fruit Pudding as an Effort to Prevent Stunting: Pemberian Makanan Tambahan (PMT) Puding Buah Naga Sebagai Upaya Pencegahan Stunting - Bunga Tiara Carolin; Dwi Novitasari; Erna Asnita; Dini Ramadhani; Eny Puji Astuti; Memes Nur Masriyah; Surya Ria Wulandari (KHD Production, 2025)
A chronic nutritional issue known as stunting is characterized by a child's height being below normal for their age. This condition is frequently brought on by a prolonged lack of dietary intake, particularly during the critical first 1,000 days of life. In an attempt to reduce stunting, this study intends to educate moms of toddlers about the health advantages of dragon fruit and how to prepare dragon fruit pudding. A literature review, pretest and posttest, lectures, and video demonstrations of how to make dragon fruit PMT are all part of this research methodology. The counseling session went well, with mothers, children, and cadres in attendance at the Posyandu apel 2 Pasar Minggu. The findings of this community service activity indicate that it was possible to raise mothers' understanding of healthy nutrition, the advantages and necessity of PMT for babies to avoid stunting, particularly PMT with dragon fruit pudding. This exercise is intended to teach participants how to make Dragon Fruit Pudding with basic materials, so that it may be utilized as a practical and adaptable stunting prevention intervention for home consumption.